Anticipation training for expert tennis players when facing a specific player - Triolet, Céline; Benguigui, Nicolas (Frontiers in Psychology, 2025)
IntroductionIn fast ball sports, such as tennis, when spatiotemporal constraints are high, players have to anticipate the opponent action. Not much is known about how players acquire and improve this ability. The aim of this study was to use an implicit training protocol (no information was given to participants) based on the knowledge of one particular opponent to analyse how experts could improve their anticipation ability.MethodProfessional tennis players were tested and trained in a protocol consisted of watching videos with temporal occlusions before the opponent stroke and guessing the direction of the stroke. Three groups took part in the experiment: one with a specific training with the same opponent as in pre- and post-tests; one with a various training with players other than the one used in pre- and post-tests (to control that the improvement is link with the knowledge of one specific opponent and not to an adaptation to the task) and one control group without practice.ResultsOnly the group trained with the same opponent increased its response accuracy.DiscussionOur results suggest that anticipation can be improved in professional tennis players with a very specific training providing information about the opponent.